A study on the availability of national centralized drug procurement in regions with different levels of economic development: an investigation and analysis of 31 provincial-level administrative regions in China - Lu, Wei; Qiao, Yan; Chen, Hongdou; Li, Wei; Wang, Menglei; Yuan, Chan; Yang, Qingqing; Lin, Yanquan; Zhao, Yuanyuan; Ye, Lu; Tang, Wan; Yuan, Zhen (Frontiers in Pharmacology, 2026)
BackgroundChina is characterized by significant regional disparities in economic development levels. Accordingly, both the regional implementation effectiveness of the national centralized drug procurement (NCDP) policy and relevant influencing factors urgently require investigation, with the aim of providing evidence to optimize the policy’s implementation.MethodsThe first to fifth batches of NCDP drugs were investigated on the basis of the adjusted standard survey methodology suggested by the World Health Organization/Health Action International. This study has assessed NCDP drug availability across over 900 secondary and tertiary public general hospitals in regions with varying levels of economic development in terms of both the procurement rate and the availability rate.ResultsThe availability of these five batches of NCDP drugs in regions with different economic development levels generally followed the pattern that their availability in developed regions is higher than that in moderately developed regions which is also higher than that in less developed regions. A significant difference was observed in the availability of different batches of NCDP drugs (P < 0.05). In developed regions, the average availability rate of each batch was relatively high (from 53.34% to 70.42%), and their procurement rates exceeded 50%. In moderately developed regions, all batches except the fourth exhibited relatively high average availability rates (from 50.08% to 65.14%), and their procurement rates all exceeded 50%. In less developed regions, only two batches (the first batch of “4 + 7” expansion and the second batch) exhibited relatively high average availability rates, and their procurement rates exceeded 50%. The availability of all types of NCDP drugs was also higher in more developed regions.ConclusionThe implementation of five batches of NCDP drugs has gained initial achievements, but differences persist among regions with varying economic development levels. Accordingly, relevant national departments should optimize the policy implementation mechanism, strengthen the construction of supply chains, and change the inertia of medical behaviour in these regions, aiming to promote the coordinated development of different regions, increase the availability of NCDP drugs and allow people to enjoy policy benefits.